Çinko-aluminyum esaslı ZA-8 alaşımında alaşım elementlerinin mekanik özelliklere ve mikroyapıya etkisi - Türk, Ahmet (Fen Bilimleri Enstitüsü, 1996)
Bu çalışmada, çinko-aluminyum esaslı ZA-8 alaşımının bileşiminde bulunan alüminyum, bakır ve magnezyum oranlarının sırasıyla, %5-ll Al, %0-3 Cu ve %0-l Mg aralıklarında değiştirilmesi ve ayrıca bu alaşıma %0,01-0,5 Mn, %0,01-0,2 Ti, %0,10-1,1 Si, %0,01-0,1 Cr ve %0,01-0,07 aralıklarında Li alaşım elementlerinin ayrı ayrı ilave edilmesi sonucu üretilen alaşımların sertlik ve çekme mukavemetleri ile 120° C sıcaklık ve 40 MPa gerilme altında sürünme davranışları belirlenmiş ve alaşımlar üzerinde yapılan metalografik çalışmalar sonucu bu özelliklerin mikroyapılar ile olan ilişkileri ortaya çıkarılmıştır. Elde edilen bu sonuçlardan, Standart ZA-8 alaşımının mevcut sertlik ve çekme mukavemetini önemli ölçüde etkilemeden sürünme direncini arttırmada etkili olan alaşım elementleri ve bunların optimum miktarları belirlenmiştir. Alaşımlarda alüminyum miktarının artması mikroyapıdaki primer p dendritlerini arttırmış ve ötektik miktarım azaltmıştır. Buna bağlı olarak alaşımların sertlik ve çekme mukavemetlerinin doğrusal bir şekilde arttığı, sürünme dayanımlarının ise sürekli olarak azaldığı belirlenmiştir. Bakır elementinin, standart alaşımın sertlik ve çekme mukavemetini %3 Cu, sürünme dayanımım ise %2 Cu oranına kadar hızla arttırdığı, %2'nin üzerindeki Cu ikvelerinin ise sürünme dayanımım önemli ölçüde etkilemediği görülmüştür. Bakır ilavesi ile incelenen mekanik özelliklerde meydana gelen yüksek orandaki iyileşmenin, bu elementin mikroyapıda oluşturduğu sCCuZru) çökelti partiküllerinden kaynaklandığı yapılan metalografik çalışmalar ile ortaya çıkarılmıştır. Mg elementi ise, sertlik değerlerinde sürekli bir artış meydana getirirken, çekme ve sürünme dayanımım %0,063 Mg oranına kadar önemli derecede arttırmış, fakat bu oranın üzerinde çekme ve sürünme dayanımlarını sürekli olarak azaltmıştır. Mekanik özelliklerde meydana gelen bu azalmaya mikroyapıda oluşan Zn-Mg2Znn ötektiğinin neden olduğu tesbit edilmiştir. İncelenen aralıkta Mn elementi standart alaşımın sürünme dayanımım sürekli ve önemli ölçüde arttırmıştır. Bu elementin standart alaşımın sertliğini ve %0,05 Mn oranına kadar da çekme mukavemetini önemli derecede etkilemediği, fakat bu oranın üzerindeki ilavelerin ise alaşımın çekme mukavemetinin azalmasına neden olduğu belirlenmiştir. Ti elementi ise, sertlik ve çekme dayanımı üzerinde önemli bir değişiklik meydana getirmez iken, %0,09 Ti değerine kadar sürünme özelliklerini olumsuz şekilde etkilemiş ve bu oranın üzerindeki Ti ilaveleri ile sürünme dayanımının arttığı tesbit edilmiştir. Mn ve Ti elementlerinin alaşımın yapışım modifiye ettiği ve mikroyapıda intermetalik bileşikler oluşturduğu gözlenmiştir. Araştırılan alaşım elementleri içerisinde, ZA-8 alaşımının sürünme dayanımım arttırmada en etkili elementin Si olduğu belirlenmiştir. Si elementi alaşımın sertlik değerleri üzerinde önemli bir etki oluşturmamasına rağmen, mukavemetin önemli oranda düşmesine neden olmuştur, ilave edilen aralıkta Cr elementinin standart alaşımın sertlik değerlerini ve %0,05 oranına kadar da çekme mukavemetini önemli derecede etkilemediği, fakat artan oranlarda ilave edilen Cr elementinin sürünme dayanımım bir miktar arttığı belirlenmiştir. Cr elementinin de Mn ve Ti elementlerine benzer şekilde alaşımın mikroyapısının modifiye ettiği ve mikroyapıda intermetalik bileşikler oluşturduğu gözlenmiştir. Li elementi ise sertlik ve çekme mukavemeti üzerinde önemli bir etki oluşturmaz iken, sürünme dayanımım oldukça azaltmıştır.

ZA-8 Alloying of zinc with aluminium, copper and other metals, in order to improve zinc properties began early in this century. The first major alloys developed for the zinc industry were the pressure die-casting alloys Zamak 3 and 5 which are traditionally associated with economic production of intricate decorative, functional or structural castings in large quantities at low cost. They have for many applications, a very desirable combination of mechanical and physical properties over other types of pressure die-casting alloys; particularly their ability to be cast by the hot chamber pressure die-cast process in which production rates are typically high, making them a cornerstone of the die-casting industry since their introduction. Thus, these alloys are used in a vast number of applications, ranging from the simplest drawer handle to the most complex precision automotive parts. Nominal compositions of these alloys are shown in the following Table 1. However, one property which sets a main limitation on their use, is their comparatively low resistance to deformation under a constant applied load, particularly in applications subjected to moderately elevated temperatures. In other words they have a low creep strength. A need for a creep-resistant alloy to meet the requirements of structural applications in the zinc industry later led to the development of improved creep- resistant alloys ILZRO 14 and 16. The composition of which is given in Table 1. Both of these alloys have creep resistance markedly superior of that of alloys Zamak 3 and Zamak 5 at all temperatures and under all conditions. High creep resistance of these alloys has been shown to be due to their alloying constituents of titanium and chromium. These elements with high melting points form a fine eutectic intergrowth of intermetallic compounds with zinc. It was shown that the presence of such particles created an effective barrier to grain growth, but most importantly increased the structural stability and creep resistance by eliminating substantial numbers of high energy, mobile grain boundaries. However, due to their low aluminium content, the other mechanical properties of these alloys are inferior to those of the conventional alloys, and they cannot be cast by the traditional hot chamber die-casting process, which severely limits their use on the market. In view of these of limitations, the zinc industry recently developed a new range of higher aluminium zinc alloys (known as ZA foundry alloys designated as ZA-8, xv ZA-12 and ZA-27) to supplement the above alloys. Compositional ranges of these three alloys according to ASTM B 86 and B 791 ingot specification are also shown in the Table 1. The evolution of this new family zinc-aluminium alloys in the market place has been rapid. Their excellent mechanical and casting properties and significant market development efforts have led to ZA alloys being specified for and increasing range of industrial application. This applies particularly to the die-casting sector where ZA alloys are being selected over traditional zinc and aluminium alloys to meet more stringent property requirements. Although originally developed as sand and gravity die-casting alloys, they can all be readily die-cast in cold chamber machines, and the alloy ZA-8, with its lower melting point and lower aluminium content, is also being routinely pressure die-cast by the traditional hot chamber die casting process, which makes this alloy, commercially, the most popular in the family. Within the family of ZA alloys, ZA-27 has the highest strength and hardness followed by ZA-12 and ZA-8. The tensile strength of ZA-27 is not significantly affected by casting techniques, whereas the tensile properties and hardness of ZA- 8 and ZA-12 are significantly higher in die cast condition. Thus, the tensile and yield strengths of ZA-8 in the gravity cast condition, are raised by close to 50% by die-casting; for ZA-12, these properties are increased by approximately 30% and 45% respectively. It is believed that these improvements are brought about principally by microstructural refinement, resulting from the fast cooling rate characteristic of the die casting process. Table 1 Chemical composition of commercial pressure diecast alloys according to ASTM B 86 and B 791 It is highly probable that ZA alloys may be used more extensively for the production of pressure die-cast components for service at elevated temperatures, where applications of conventional zinc alloys are usually limited because of their poor resistance to creep. At these temperatures the creep properties are more important than the short-term tensile properties and have become a major concern as a limiting factor in design. As far as the creep is concerned, ZA-8 alloy has a substantially better creep performance than the others in the family of ZA alloys, which commercially makes this alloy even more attractive But, unfortunately this XVI Chromium, which was studied in the addition range between 0.01% and 0.10%, had similar effect on the mechanical and microstructure of the ZA-8 alloy in that this element did not also much change the hardness and tensile strength, continuously increased the creep strength in the range studied. This element also strongly modified the microstructure and was found to be present in the forms of Al-Cr intermetalic particles in the eutectic regions. Lithium was added to the standard alloy in the range from 0.01% to 0.07%. It was found that although this element did not much effect on the hardness and tensile strength, its effect on the creep strength was disastrous. This was found to be due to degenerated eutectic morphology and the gas porosity brought about by additions of lithium element. xix probably did not have much strong effect in increasing the creep resistance of the alloys, and therefore increasing the copper content above 2% produced very little further creep resistance. Increased copper, on the other hand, increased the amount of the eutectic with regular lamellar morphology in the alloys, producing more r) sites in which e(CuZn4) phase precipitates. Thus, the regular eutectic morphology combined with the strong strengthening effect of copper additions was thought to be responsible for high creep resistance in these alloys. The other minor alloying element present in the composition of the ZA-8 alloy had an effect on the mechanical properties investigated as such that additions of magnesium element up to 0.063% increased all the mechanical properties investigated. Additions of this element higher than this continued to increase the hardness, but caused sharp decreases in the tensile and creep strength. As a result of the metallografic studies, it was found that these sharp decreases in the mechanical properties were due to the Zn-Mg2Znn eutectic phase which was observed in the alloys containing high magnesium. The manganese, which was added to the ZA-8 alloy in the range from 0.01% to 0.5%, did not have much effect on the hardness of the ZA-8 alloy, but slightly increased the ultimate tensile strength up to 0.05% Mn. Further additions of this element, however, caused the tensile strength to decrease. On the other hand, this element was the most effective element in increasing the creep resistance of the ZA-8 alloy after silicon, and creep resistance of the ZA-8 alloy increased continuously with increasing manganese. Metallografic examinations showed that manganese strongly modified the microstructure and caused the eutectic volume to increase in more regular form. In the alloys containing high amount of manganese, this element formed Al8Mn5 intermetalic compounds. The effect of the silicon on the mechanical properties of the ZA-8 alloy was investigated in the range varying from 0.10% to 1.1%. It was found that this element was the most effective element in increasing the creep strength of the ZA- 8 alloy. Additions of Si increased the creep resistance sharply up to approximately 0.20%. Further additions also increased the creep strength, but at much reduced rates. However, although this element slightly increased the hardness, it caused substantial decreases in the tensile strength, in such manner that the higher the silicon the lower the strength. Metallografic studies showed that the changes in the mechanical properties brought about by additions of the silicon was due to the increased eutectic grain size, directional growth of the dendrites and Si particles at the p/eutectic interface. Titanium alloying element was added to the standard ZA-8 alloy in the range from 0.01% to 0.20%. This element did not much change the hardness and tensile strength of the standard alloy. But, it decreased the creep strength of the standard alloy when added below 0. 10%, further additions above that sharply increased the creep strength. It was found that Ti strongly modified the microstructure of the standout alloy, and formed TiZn15 intermetalic compound which was particularly observed in the dendrites. XV1H Chromium, which was studied in the addition range between 0.01% and 0.10%, had similar effect on the mechanical and microstructure of the ZA-8 alloy in that this element did not also much change the hardness and tensile strength, continuously increased the creep strength in the range studied. This element also strongly modified the microstructure and was found to be present in the forms of Al-Cr intermetalic particles in the eutectic regions. Lithium was added to the standard alloy in the range from 0.01% to 0.07%. It was found that although this element did not much effect on the hardness and tensile strength, its effect on the creep strength was disastrous. This was found to be due to degenerated eutectic morphology and the gas porosity brought about by additions of lithium element.
Tez (Doktora)-- İTÜ Fen Bil. Enst., 1996.
Keywords: Alaşımlar; Alüminyum; Mekanik özellikler; Mikroyapı; Çinko; Alloys; Aluminum; Mechanical properties; Microstructure; Zinc